CD163(+)/CD68(+) tumor-associated macrophages in angiosarcoma with lymphedema - Du, Xuemei (Int J Clin Exp Pathol, 2018)
Angiosarcoma of soft tissue is a group of aggressive malignancies with high mortality. However, molecular pathogenesis and therapeutic targets of angiosarcoma remain to be established. We explored the influence of M2-polarized tumor-associated macrophages (TAMs) on the formation of angiosarcoma. CD163(+)/CD68(+) macrophages were determined by immunohistochemistry from a series of 38 samples, including 17 cases of angiosarcoma with lymphedema and 21 cases of lymphangioma. The number of CD163(+)/CD68(+) macrophages in angiosarcoma was significantly higher than that in lymphangioma. VEGFc was universally expressed in both angiosarcoma tumor cells and CD163(+)/CD68(+) macrophages. VEGFR3 was expressed only in angiosarcoma tumor cells. Our study indicates a potential role of TAMs in the development of angiosarcoma with lymphedema. The VEGF signaling pathway may thus serve as a potential target for treatment of angiosarcoma.